Lactoferrin Glu561Asp facilitates secondary amyloidosis in the cornea. Issue 6 (27th May 2005) - Araki-Sasaki, K; Ando, Y; Nakamura, M; Kitagawa, K; Ikemizu, S; Kawaji, T; Yamashita, T; Ueda, M; Hirano, K; Yamada, M; Matsumoto, K; Kinoshita, S; et al.
Abstract : Aim: To elucidate the pathogenic mechanism of amyloid formation in corneal amyloidosis with trichiasis. Methods: Ophthalmological examination was performed in nine patients to determine secondary corneal amyloidosis with trichiasis. Congo red staining and immunohistochemistry using anti-human lactoferrin antibody were used for biopsied corneal samples. For genetic analyses, single strand conformation polymorphism (SSCP), direct DNA sequence analysis, and polymerase chain reaction (PCR) induced mutation restriction analysis (IMRA) were employed to detect lactoferrin gene polymorphism. Results: All patients had had trichiasis at least for 1 year, and all amyloid-like deposits were found in one eye with trichiasis. Ophthalmological examination revealed that eight patients showed gelatinous type of amyloid deposition and one showed lattice type of amyloid deposition. Studies of biopsied corneal samples with Congo red stain revealed positive staining just under the corneal epithelial cells. Immunoreactivity of anti-human lactoferrin antibodies was recognised in all tissues with positive Congo red staining. Lactoferrin gene analysis revealed that seven patients were heterozygotic and two were homozygotic for lactoferrin Glu561Asp. The frequency of the polymorphism in the patients was significantly different from that in 56 healthy control subjects. Conclusion: Lactoferrin Glu561Asp is a key polymorphism related to facilitating amyloid formation in corneal amyloidosis with trichiasis.